Opinions of 6th year students of the Faculty of Medicine on the process of their education in Pomeranian Medical University - Gąsiorowski, Jakub; Radlińska, Iwona; Kolwitz, Marcin; Kładna, Aleksandra (Polish Journal of Public Health, 2009)
Introduction. Medical studies have the opinion of being difficult and requiring lots of devotion. Experiences gathered during the studies influence the professional profile of future physicians. Aim. The aim of this work was to learn opinions of the students of the Faculty of Medicine of PMU completing their sixth year of studies on their education process and the impact of gathered experiences on themselves. Material and method. The group of 113 of all 119 students of 6th year, the Faculty of Medicine of PMU in the academic year 2004/2005 were anonymously interviewed. Results. For the half of the respondents (51%) the vision of the studies appeared to be consistent with the reality, slightly fewer (49%) had the opposite opinion. The critical comments were often related to too little amount of practical classes (29% of the respondents raised this issue) and on the other hand too much theory (according to 20% of the respondents). The most insatiable tudents’ expectations were related to the lack of contact with the academic teachers (22% of the respondents were not satisfi ed and 64% were partially satisfi ed), followed by a technical infrastructure (14% were not satisfi ed and 77% partially satisfi ed). Most of the students (83%) noticed changes in themselves – both positive and negative. The most common negative changes were: despair in the ideal of the physician’s work (18 cases), pessimistic and cynical attitude to the future (13 cases). The most common positive changes were: the increase of the openness on the other (15 cases), reaching personal maturity (14 cases) and gathering a richer look at other people (12 cases). Over ¼ (28%) of the respondents would not take the medical studies if they have a second chance. Conclusions. The crisis of the relation academic teacher – student appears to be the most important factor infl uencing the lack of fulfi llment of the expectations with the medical studies. Further studies and actions are recommended to heal the process of undergraduate education of future doctors.